Working-class diet and health in Nottingham, 1850-1939 - Amos, Denise M. (2000)
The rise in population together with industrialisation in the first half of the nineteenth century presented central government and local authorities with new challenges. Large numbers of people crowded together in poorly constructed homes with very limited sanitation facilities and created the perfect breeding ground for infectious diseases. The endemic nature of many of these diseases affected the most vulnerable members of society and the reduction in the high death-rates was an important consideration for the authorities.